Gendered paths to asset accumulation? Markets, savings, and credit in developing countries - Catanzarite, Zachary; Diana, Carmen Diana; Doss, Cheryl D.; Oduro, Abena D.; Suchitra, J. Y.; Swaminathan, Hema (Feminist Economics, 2019)
An extensive literature shows how property inheritance is biased against women in many developing countries, yet relatively little attention has been given to gender bias in other means of acquiring physical assets, such as the market. Using individual-level data from Ecuador, Ghana, and Karnataka, India, this study analyzes modes of acquisition and financing of housing, agricultural land, other real estate, and businesses. The findings show that women acquire fewer of their assets through the market than men, and that in asset markets, both men and women are more likely to use their own savings than to use credit. The study also analyzes current loans for asset acquisition and finds that, in general, women tend to be somewhat disadvantaged in securing formal bank loans. The results suggest that financial inclusion to promote more gender equal access to accumulation of assets should focus on both savings and credit, with priority to savings.
https://www.feministeconomics.net
Keywords: OFDIG; afrique; amériques; approches et analyses; asie; discipline; femmes*; inégalités; microcrédit; ressource en ligne; régions géographiques; sciences de la gestion; systèmes d'oppressions; économie

L’économie solidaire sous le prisme du genre: une analyse critique et possibiliste - Guérin, Isabelle; Hillenkamp, Isabelle; Verschuur, Christine (Revue Française de Socio-Économie, 2019)
Cet article propose d’étudier l’économie solidaire sous le prisme du genre à partir d’un double regard, critique et possibiliste. Ce double regard, inspiré à la fois de l’économie substantive polanyienne et des recherches féministes, éclaire la manière dont les pratiques d’économie solidaire renouvellent l’économique et le politique, compris ici à la fois comme catégories d’action et de pensée. Il met aussi en lumière les chemins multiples et sinueux de l’émancipation, fruit d’un entremêlement entre principes d’échange dont l’équilibre est en renouvellement permanent.
https://rfse.univ-lille.fr
Keywords: OFDIG; approches et analyses; discipline; genre; identités LGBTQIA2+; inégalités; pouvoir; ressource en ligne; sciences de la gestion; systèmes d'oppressions; thématiques; économie; économie solidaire